(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
In this era of globalization, the problem of human resources has become one of the problems that affects the resilience of an agency. The importance of managing human resources is caused by humans themselves who are the main actors in activities aimed at achieving the success of an agency’s goals. Researchers use quantitative research to analyze data descriptively using descriptive analysis methods. The respondents of this research were all 100 BKPP Semarang City employees. The method used by researchers in selecting samples in this research is nonprobability sampling with a saturated sampling category. This data analysis technique uses Smart Pls4 to process the data. The results of this research show that the work discipline variable has a significant effect on work motivation. The work environment has a significant effect on motivation. Work discipline has a significant effect on employee performance. The work environment has a significant effect on employee performance. Work motivation has a significant effect on employee performance. Work discipline and work motivation have a significant effect on employee performance. The work environment and work motivation have a significant effect on employee performance